Synergistic Antimicrobial Activity of Silver Nanoparticles with an Emergent Class of Azoimidazoles - Ana Isabel Ribeiro; Bárbara Vieira; Daniela Dantas; Bárbara Silva; Eugénia Pinto; Fátima Cerqueira; Renata Silva; Fernando Remião; Jorge Padrão; Alice Maria Dias; Andrea Zille (MDPI AG, 2023)
The combination of two or more agents capable of acting in synergy has been reported as a valuable tool to fight against pathogens. Silver nanoparticles (AgNPs) present a strong antimicrobial action, although their cytotoxicity for healthy cells at active concentrations is a major concern. Azoimidazole moieties exhibit interesting bioactivities, including antimicrobial activity. In this work, a class of recently described azoimidazoles with strong antifungal activity was conjugated with citrate or polyvinylpyrrolidone-stabilized AgNPs. Proton nuclear magnetic resonance was used to confirm the purity of the compounds before further tests and atomic absorption spectroscopy to verify the concentration of silver in the prepared dispersions. Other analytical techniques elucidate the morphology and stability of AgNPs and corresponding conjugates, namely ultraviolet-visible spectrophotometry, scanning transmission electron microscopy and dynamic light scattering analysis. The synergistic antimicrobial activity of the conjugates was assessed through a checkerboard assay against yeasts (Candida albicans and Candida krusei) and bacteria (Staphylococcus aureus and Escherichia coli). The conjugates showed improved antimicrobial activity against all microorganisms, in particular towards bacteria, with concentrations below their individual minimal inhibitory concentration (MIC). Furthermore, some combinations were found to be non-cytotoxic towards human HaCaT cells.